2016
DOI: 10.1007/s11423-016-9446-5
|View full text |Cite
|
Sign up to set email alerts
|

Teachers and technology: development of an extended theory of planned behavior

Abstract: This study tests the validity of an extended theory of planned behaviour (TPB) to explain teachers' intention to use technology for teaching and learning. Five hundred and ninety two participants completed a survey questionnaire measuring their responses to eight constructs which form an extended TPB. Using structural equation modelling, the results showed that the constructs in the extended TPB were significant in explaining teachers' intention to use technology in their work. Among the constructs in the rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
1
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 72 publications
8
40
1
16
Order By: Relevance
“…However, although widely used, over the years, the TPB has suffered various criticisms due to its presumed poor predictive efficacy, related, in particular to the use of an insufficient number of variables to explain the reasons pushing individuals to undertake a given behavior in certain circumstances [14][15][16].…”
Section: The Birth Of the Theory Of Planned Behaviormentioning
confidence: 99%
“…However, although widely used, over the years, the TPB has suffered various criticisms due to its presumed poor predictive efficacy, related, in particular to the use of an insufficient number of variables to explain the reasons pushing individuals to undertake a given behavior in certain circumstances [14][15][16].…”
Section: The Birth Of the Theory Of Planned Behaviormentioning
confidence: 99%
“…While TPB is useful in its original specification, [1] it was put forth that, after the examination of traditional TPB variables, the TPB can allow additional predictors if these additional constructs can capture a significant proportion of the variance in intention. In fact, the initial TPB model has been criticised throughout its life for insufficient predictive power, criticisms related fundamentally to the use of an inadequate number of variables capable of explaining the reasons that lead individuals to have certain behaviours [12][13][14]. This has led many analysts to modify the original theoretical model by adding to the basic explanatory variables (attitudes, subjective norms and PCB), additional variables that have been shown in some cases to have a certain explanatory capacity such as, for example, "past behaviour", "moral norms", "perceived moral obligation", "perception of ease of use", "capacity to reject" and others [15].…”
Section: The Theory Of Planned Behaviourmentioning
confidence: 99%
“…The UTAUT has also served as a lens to understand how technology is adopted for technologies such as collaborative tools (Yueh et al 2015), online learning (Lakhal et al 2013;Marchewka et al 2007), and interactive whiteboards (Tosuntaş et al 2015). When exploring behavioral intent to employ technology, variables such as perceived ease of use (Teo 2014), subjective norms (Hao et al 2017), attitudes (Blackwell et al 2013;Teo et al 2016), and facilitation conditions (Wong 2016) have all been found to play a role in how teachers employ technology. Despite the numerous factors of the UTAUT, many studies suggest caution due to the highly contextualized nature of learning technologies integration (ElMasri and Tarhini 2017;Teo 2014;Wong 2016).…”
Section: Technology Acceptance and Integrationmentioning
confidence: 99%
“…Moreover, much of the extant research on mobile learning has been approached from a higher education perspective (Wu et al 2012). Although studies have begun to explore mobile technologies, less is known about the degree to which these are integrated in classroom contexts (Gunter and Reeves 2016;Nikou and Economides 2017;Teo et al 2016). Ifenthaler and Schweinbenz (2013) further argued that limited research exists regarding how in-service teachers integrate mobile technology in the classroom using the UTAUT framework.…”
Section: Research Questionsmentioning
confidence: 99%